The Concept of Morality (sīla) in Buddhism - Mahathero, Sankichcha (Dhammacakka Journal of Buddhism and Applied Buddhism, 2025)
Background: Virtue (sīla) is the fundamental foundation for achieving Nirvana in Buddhism. It is a set of moral conduct which is essential for the holistic life of an individual, a small unit of an ideal society. sīla also is a very essential factor for bringing transformation in the human societies. Practices of virtue (sīla) opens the door for Samadhi and Panna respectively. Objective: This article explores the method of mental purification by means of Virtue, the code of ethical behavior. Methodology: Expository or Descriptive approach is applied while writing this paper. Result: sīla includes refraining from killing, taking what is not given, sexual misconduct, lying, slandering, harsh speech, talking nonsense, covetousness, malevolence and wrong view, which are regarded as unwholesome deeds. A thorough observance of sīla leads one to peace, prosperity, social reputation and happiness in this life. It also helps a person to have a tranquil exit from the world. It is directed to bodily, mental and verbal purity. Conclusion: The benefits of practicing sīla, including ethical wellbeing, a favorable rebirth, and ultimate liberation, are discussed in the article. Besides, the article also emphasizes on sīla being safeguard to human being opining all golden gates leading one to spiritual progress or ultimate goal of human being i.e. enlightenment.